FINANCIAL ANALYSIS OF TOURISM, RESTAURANT, HOTEL COMPANIES: PRE- PANDEMIC AND COVID-19PANDEMIC PERIOD - Angel Febiyanti; Rini Tri Hastuti (Graduate Program of Universitas Tarumanagara, 2024)
This research aims to evaluate the differences in the financial condition of companies in the hotel, restaurant and tourism sub-sectors listed on the Indonesia Stock Exchange during the pre-pandemic period (2018-2019) and in the midst of the Covid-19 pandemic (2020-2021). Using three financial indicators (liquidity, profitability, and solvency), the research involved 120 samples from 10 companies using purposive sampling. Through a quantitative approach and data analysis using Microsoft Excel and SPSS 26 with paired sample t-test, the research findings indicate variability in financial performance, measured through the Current Ratio (CR), Return on Assets (ROA), and Debt to Equity Ratio (DER), between the pre-pandemic and Covid-19 pandemic periods. The implication is to provide in-depth understanding and crucial insights for business practitioners and stakeholders in maintaining the corporatefinances through financial ratio analysis, especially in facing unpredictable economic dynamics.